The trend of opioid prescriptions among cancer patients in a tertiary hospital: A multimethod quantitative study - Limsomwong, Pawita; Ingviya, Thammasin; Fumaneeshoat, Orapan (Frontiers in Oncology, 2023)
Objectives: To assess the trends and factors associated with opioid prescriptions for cancer patients in Songklanagarind Hospital, the largest referral center in Southern Thailand. Design: Multi-method quantitative study Methods: We reviewed the electronic medical records of 20,192, outpatients aged ≥18 years diagnosed with cancer between 2016 and 2020 who received opiod prescriptions. Oral morphine equivalents (OME) were calculated using the standard conversion factors and the OME trend during the study period was assessed by a generalized additive model. Factors affecting the morphine equivalent daily dose (MEDD) were assessed using multiple linear regression with a generalized estimating equation. Results: The mean overall MEDD for all study patients was 27.8±21.9 mg per day per patient. The bone and articular cartilage cancer patients had the highest MEDD. For every 5-year increase in the duration of cancer, the MEDD increased by 0.02 (95% confidence interval [CI]: 0.01 - 0.04). Patients with stage 4 cancer received a higher average MEDD of 4.04 (95% CI: 0.30-7.62) as compared to those with stage 1 cancer. Patients with bone metastasis received a average higher MEDD of 4.03 (95% CI: 0.82-7.19) compared to those without. Age was inversely associated with the MEDD. Patients aged 42-58, 59-75 and >76years old received MEDDs of 4.73 (95% CI: 2.31-7.15), 6.12 (95% CI: 3.66-8.59) and 8.59 (95% CI: 6.09-11.09) compared with those aged 18-42 years old. Brain metastasis was inversely associated with MEDD of 4.49 (95% CI: 0.61-8.37) compared to those without. Conclusion: Opioid use in cancer patients in this study is lower than the average global usage. Promoting opioid prescriptions for pain management through medical education can help doctors overcome opiophobia.